2015
DOI: 10.1146/annurev-med-052912-123749
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the RV144 Thai Phase III HIV-1 Vaccine Trial and the Search for Correlates of Protection

Abstract: RV144 remains the only HIV-1 vaccine trial to demonstrate efficacy against HIV-1 acquisition. The prespecified analysis of immune correlates of risk showed that antibodies directed against the V1V2 region of gp120, in particular the IgG1 and IgG3 subclass mediating antibody-dependent cell-mediated cytotoxicity, seem to play a predominant role in protection against HIV-1 acquisition and that plasma envelope (Env)-specific IgA antibodies were directly correlated with risk. RV144 and recent nonhuman primate chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
140
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(144 citation statements)
references
References 93 publications
(118 reference statements)
2
140
0
2
Order By: Relevance
“…Identifying the immune correlates of protection against HIV/SIV continues to be a central pursuit for the vaccine research community (29)(30)(31). Multiple vaccine studies in NHPs and humans have implied that functional antibody responses against Env are necessary for protective immunity (3,18,32).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the immune correlates of protection against HIV/SIV continues to be a central pursuit for the vaccine research community (29)(30)(31). Multiple vaccine studies in NHPs and humans have implied that functional antibody responses against Env are necessary for protective immunity (3,18,32).…”
Section: Discussionmentioning
confidence: 99%
“…Attenuated form of vaccine shows the strongest method to induce the protection in many NHP [109]. But in human testing, this research is ruled out due to safety [106,107].…”
Section: Developmental Study Of Hiv Vaccinementioning
confidence: 98%
“…The pre-specified immune correlates analysis showed that antibodies which are used against the gp120's region of V1V2 possesses an important role to protect from acquirement of HIV-1 and that envelope of plasma which is Env-specific IgA form of antibodies correlates directly with the risk [109].…”
Section: Developmental Study Of Hiv Vaccinementioning
confidence: 99%
“…48 Subsequently a number of studies further exploring the potential mechanisms of protection of RV144 have been performed. [50][51][52] Sieve analysis comparing sequences of breakthrough virus isolates found that isolates from vaccine recipients were less likely to have a lysine at K169 of the Env V2 region than placebo recipients, suggesting selective effects of vaccine induced immune responses on V1V2 on breakthrough HIV-1 viruses. 53 Further characterization of RV144 vaccine-induced V2 Ab found that the Ab recognized both conformational (on gp70-V1V2) and linear epitopes (residues 165-178, immediately N-terminal to the putative a4b7 binding motif in the mid-loop region of V2) and were cross-reactive with the V1V2 regions from many HIV-1 subtypes (A, B, C and CRF01_AE).…”
Section: Rv144mentioning
confidence: 99%